Temporal patterns and individual characteristics of compulsory treatment orders for mental disorders in Scotland from 2007 to 2020 - Lisa Schölin; Rohan Borschmann; Arun Chopra (BJPsych Open)
Background Compulsory mental health treatment has increased globally. In Scotland, compulsory treatment for >28 days is permitted under hospital- and community-based compulsory treatment orders. Community-based compulsory treatment has not been shown to lead to improved outcomes, and scrutiny of their use is needed.